Potential unintended consequences of graphic warning labels on sugary drinks: do they promote obesity stigma? - L. E. Hayward; L. R. Vartanian (Wiley, 2019)
Summary Introduction Public health interventions need to balance the benefits with any potential harms. One proposed intervention for reducing sugar‐sweetened beverage consumption involves placing graphic warning labels on products and advertisements. A recent study found that a graphic warning label that contained negative imagery of obesity reduced purchases of sugar‐sweetened beverages. However, these labels may also promote obesity stigma, which is concerning given that weight stigma is associated with harmful health consequences including weight gain and increased risk of mortality. Methods In Study 1 (n = 681), participants viewed a standard soda label or the graphic warning label online and then completed measures of disgust and prejudice towards people with obesity. In Study 2 (n = 506), participants who identified as having overweight or obesity viewed the graphic warning label online before or after completing measures of mood and state self‐esteem. Results In Study 1, participants who had viewed the graphic warning label reported higher disgust and weight bias. In Study 2, the majority of participants perceived the warning label to be stigmatizing, and participants displayed worse mood and, through this, lower self‐esteem after viewing the label. Conclusions Although the graphic warning label has been found to reduce sugary drink purchases, it also promotes obesity stigma and is perceived as stigmatizing by individuals with overweight and obesity. Given that weight stigma predicts harmful health and well‐being consequences, the benefits of graphic warning labels need to be balanced against the potential costs.